Auditors’ Communication with Audit Committee: Evidence from Indonesia - Eliza Fatima; Sylvia Veronica Siregar; Vera Diyanty (Universitas Pendidikan Ganesha, 2022)
The aim of this study is to explore the auditors’ communication with those charged with governance (TCWG). Specifically, we examine the communication between auditors and the audit committee on the audit of financial statements in the year 2020 in the Indonesian setting. We use questionnaires to collect the data. Our samples are 72 audit committee members from various industries. We find that most of the auditors have discussed the matters that are required by the audit standards. However, we find that almost ten percent of the respondents reported that there was no kick-off meeting before the start of the audit process. The absence of a kick-off meeting may indicate that the audit plan is not communicated in a timely manner to the audit committee. We also find that face-to-face communication through a meeting is preferred to written communication most of the time.